Insilico Analysis of the Potential Phytoestrogens of Selected Alkaloid from ‎Soursop (Annona muricata) Leaves - Fitriyah, Fitriyah; Fitria, Aida; Wardhani, Hilda Aqua Kusuma (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2021)
Estrogen is an important hormone in the female reproductive system, as well as other systems in men and women. The decrease of estrogen levels mainly occurs in the menopause phase. The decrease of estrogen is one indication of the presence of various diseases such as cardiovascular disease. Decreased levels of estrogen can be treated by administering exogenous estrogen such as Estradiol-17β. However, long-term administration of estradiol plays an important role in tumor cell growth. Phytoestrogens are plant-basedpolyphenolic compounds that have a structure and biological activity similar to the estrogen. Phytoestrogens can be derived from alkaloid compounds, one of which is found in the soursop (Annona muricata) leaves. The purpose of this study was to analysis the potential phytoestrogens of selected alkaloid in the A. muricata leaves. The analysis was carried out using the insilico approach using molecular docking methods, pharmacokinetic analysis and druglikeness. The molecular docking results showed that the ligands could bind to the receptors on the specific binding site with the lowest binding affinity value approaching the control ligands, namely the Anonaine compound of -8.6 kcal / mol, followed by Xylopine compound of -7.8 kcal / mol and Annonamine of -7.0 kcal / mol. The results of pharmacokinetic and druglikeness showed that all ligand compounds have a good ability to be absorbed in the gastrointestine and have a good bioavalaibility as an oral drug.